(untitled) (Global Journal of Human-Social Science, 2014)
Introduction-The present paper deals with cognitive-discursive analysis of the models of Russia’s future in political discourses of the Russian Empire, the British Empire and the United States (middle of the XIX th century -beginning of the XX th century). The author’s aim is to look through the text at the part of «the past reality» that lies behind this text and at the model of future constructed in it studying «not only where History was, but also where History is going» [2] and could be going and even could have gone.